2008
DOI: 10.1007/s00204-008-0297-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transferrin and hepcidin genes expression in the liver of the fish Pseudosciaena crocea following exposure to cadmium

Abstract: Water pollution of heavy metals such as cadmium is a serious problem in China. Cadmium is toxic to cellular processes such as the transport and metabolism of iron. The nucleotide sequences of serum transferring (c-sTf) and hepcidin (c-Hep) genes from croceine croaker (Pseudosciaena crocea) were determined. The full-length cDNAs of c-sTf and c-Hep were 2,486 and 850 nt, respectively. After cadmium exposure (CdE), fish serum iron increased significantly and reached a high level at 24 h, after which it decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…Numerous previous studies have revealed deleterious actions of Cd in diverse systems and models (2-5); however, relatively few studies have attempted to determine the potential biological effects of exposure to chronic sublethal Cd levels. Increasing evidence has suggested that Cd may affect the homeostasis of essential metals, through competition or other unknown mechanisms (34,35). Cd burden was previously shown to stimulate the expression of divalent metal transporter 1 in enterocytes (36).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous previous studies have revealed deleterious actions of Cd in diverse systems and models (2-5); however, relatively few studies have attempted to determine the potential biological effects of exposure to chronic sublethal Cd levels. Increasing evidence has suggested that Cd may affect the homeostasis of essential metals, through competition or other unknown mechanisms (34,35). Cd burden was previously shown to stimulate the expression of divalent metal transporter 1 in enterocytes (36).…”
Section: Resultsmentioning
confidence: 99%
“…Transferrin saturation could function as a signal for iron balance maintenance mechanisms. In a cadmium exposure study, changes in the expression of transferrin genes in the liver of the fish Pseudosciaena crocea were shown subsequent to cadmium exposure 25 . In our subtractive hybridization, three transferrin clones were found, and the mRNA expression levels of transferrin were altered in the group exposed to BaP.…”
Section: Dose-dependent Gene Expression Of Cytochrome P450 1a In Bap mentioning
confidence: 99%
“…It is synthesized by the hepatic cells and secreted into the blood, and level of transferrin saturation may act as a signal for mechanisms that maintain iron balance. The recent study showed the induction of transferrin mRNA in liver upon exposure to cadmium 33 . Similarly, we found that B[k]F exposure resulted in transcriptional change of transferrin gene compared with non-exposed control group (Table 1).…”
Section: Cell Defense Mechanismmentioning
confidence: 99%